Pengaruh Exchange Rate dan GDP Terhadap Ekspor dan Impor Indonesia - Adi, Lumadya (Develop, 2017)
The purpose this research is to examine the impact of Exchange Rate and GDP on Indonesia’s Export and Import. Tools analysis is Dynamics Ordinary Least Square (DOLS): Error Correction Model (ECM). The result are: 1. GDP influence positif and significant in short-term and longterm relationship on Indonesia’s impor; 2. Exchange Rate influence positif and significant in short-term and longterm relationship on Indonesia’s impor; 3. GDP influence positif and significant in short-term but negatif and significant in longterm relationship on Indonesia’s export; 4. Exchange rate influence positif and significant in short-term but negatif and significant in longterm relationship on Indonesia’s export.Keywords: error correction model, gdp, exchange rate, impor, ekspor